STRENGTHENING THE RECOGNITION OF THE RIGHTS OFPHYSICALLY CHALLENGED PERSONS UNDERINTERNATIONAL HUMANITARIAN LAW: MOVING BEYONDHUMANITARIAN PARADIGM (IUS LAW Journal, 2025)
Arguably the adoption of the Convention on the Rights of Persons with Disabilities represents animportant progressive development in the protection framework accorded to physicallychallenged persons under International Humanitarian Law. The objective of this paper is toexamine the extent of protection accorded to physically challenged persons from harm insituations of risk consistent with International Humanitarian Law. The paper argued thatexamining the applicable legal and policy framework aimed at protecting the rights of physicallychallenged persons under international humanitarian law is not only a programmatic goal to beattained in the long term, but rather an immediate task on Countries to adopt measures in thiswithout delay. This is against the backdrop driven by the desire to create stability between therules of International Humanitarian Law(IHL) and the Convention on the Rights of Persons withDisabilities(CRPD) both in times of peace and armed conflict. It is therefore important toreiterate the fact that if the future of physically challenged persons must be guaranteed, the needto take cognizance of their peculiarities must not be overlooked. It is therefore advanced that thecontinued neglect of peculiarities of physically challenged persons both under the Conventionand International Humanitarian Law portends a clog in the general protection against the effectsof armed conflict or humanitarian emergencies. This paper adopts an analytical and qualitativeapproach and built its argument on existing literature which is achieved by a synthesis of ideas.Nevertheless, this article provides some recommendations that will guarantee special protectionto physically challenged persons derivable from the principle of humanity.
Keywords: Physically Challenged, Persons, Rights, International, Humanitarian Law.